A Gary Larson of the 1750s? Niels Krog Bredal's "Dreamworld" - Aspaas, Per Pippin (UiT The Arctic University of Norway, 2017)
Presentation from the 2nd Nordic Conference in Eighteenth-Century Studies, Uppsala 12–14 October 2017. In March 1753, a curious Latin text, titled “ΟΝΕΙΡΟ-ΚΟΣΜΟΣ. Id est Mundus in Somnio, Poëma Philosophico-Heroicum” [The Dreamworld, a Philosophical-Heroic Poem] appeared in the prestigious Copenhagen weekly, Nye Tidender om Lærde og Curieuse Sager. In a mixture of dactylic hexameters and prose, it deals with a world that the poet has “visited” during his sleep, or rather, in a state of ecstasis, when he was neither asleep nor awake. The hero of the ecstasis suddenly finds himself in a world whose inhabitants speak an unintelligible language. Despite initial complications, he manages to befriend them and study their society as well as the natural history of their planet. Upon waking up, the author interprets his own dream as proof that humanity is not the only lifeform to have souls. The author, Niels Krog Bredal, was only 19 at the time; the satiric “Dreamworld” was his debut. Replete with irony and self-mockery, it may not be taken too seriously. Nevertheless, like the cartoons of Gary Larson, Bredal’s “Dreamworld” contains grotesque elements that are clearly meant not only to evoke laughter, but also to undermine established ways of thinking about, and dealing with, our fellow beings. It may therefore merit a place in the history of philosophical debates on the superiority of humankind over other species. In my presentation, I will first discuss the “Dream Genre” in early modern literature, then present the contents of Bredal’s text in some detail, and finally analyze it as an example of the “Conte Philosophique”, a genre made popular by the likes of Voltaire.